2017
DOI: 10.1016/j.msea.2017.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zirconia and iron on the mechanical properties of Al2O3/TiC composites processed using combined self-propagating synthesis and direct consolidation technique

Abstract: Self-propagating high temperature synthesis combined with direct consolidation technique was used to synthesize high density Al 2 O 3 /TiC composites from mixture of TiO 2 , Al and graphite powders. The effect of controlled amount of zirconia and iron addition on the density, microstructure and the mechanical properties of the composites was investigated. The results revealed that, addition of either 1.0 mole zirconia or 5.0 wt% of iron metal powder led to a significant decrease in the sample porosity from 7.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Table 1 lists the heat-releasing parameters of samples, the S4 comprised of EG and Ti exhibits the highest FGI value of 0.42 kW·m −2 ·s −1 , while the S3 presents the lowest FGI of 0.08 kW·m −2 ·s −1 (the same to that of S5), implying that the CB or VG inhibits the flame propagation effectively [14,15]. Because the EG transforms into fluffy worm-like structure with a vigorous expansion, it facilitates the propagation of combustion wave and heat transfer further due to the loose and fluffy stacking, which favors an extremely vigorous and energetic process [17], evidenced by the decrease in TTI and the rapid increase in HRR. However, the mercerization of NaOH favors the purification of carbon allotropes; the impurities could have transformed combustible volatiles and produced a higher heat release, evidenced by the decrease in the THRs for samples with carbons after NaOH-impregnation.…”
Section: Hrr Of Ti Blended With Different Carbon Allotropesmentioning
confidence: 86%
“…Table 1 lists the heat-releasing parameters of samples, the S4 comprised of EG and Ti exhibits the highest FGI value of 0.42 kW·m −2 ·s −1 , while the S3 presents the lowest FGI of 0.08 kW·m −2 ·s −1 (the same to that of S5), implying that the CB or VG inhibits the flame propagation effectively [14,15]. Because the EG transforms into fluffy worm-like structure with a vigorous expansion, it facilitates the propagation of combustion wave and heat transfer further due to the loose and fluffy stacking, which favors an extremely vigorous and energetic process [17], evidenced by the decrease in TTI and the rapid increase in HRR. However, the mercerization of NaOH favors the purification of carbon allotropes; the impurities could have transformed combustible volatiles and produced a higher heat release, evidenced by the decrease in the THRs for samples with carbons after NaOH-impregnation.…”
Section: Hrr Of Ti Blended With Different Carbon Allotropesmentioning
confidence: 86%
“…Furthermore, it was reported that combining glass and ceramic materials together in one composite structure results in a new polycrystalline material with desirable properties and tailored applications (Ahmed et al 2017 ; Besisa and Ewais 2019 ). The type and properties of the inserted ceramic materials can determine the final characteristics and the new applications of the original glass (Sandu et al 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%